Numerical modelling of elasto-plastic friction in bow–string interaction with guaranteed passivity - Matusiak, Ewa; Chatziioannou, Vasileios; Van Walstijn, Maarten (Frontiers in Signal Processing, 2025)
In order to simulate the function of bowed string instruments, it is necessary to model the frictional interaction between the bow hair and the vibrating string. This is possible using an elasto-plastic friction model, which has previously succeeded in reproducing experimental data captured on a monochord setup. In this study, this elasto-plastic model is refined to guarantee passivity, and a stable numerical scheme is derived that inherits the energy balance of the underlying continuous model. The approach presented considers a finite-width bow, thus spreading the bow–string interaction over an area. The compliance of the bow hair and the torsional motion of the string are also taken into account. A sound example and animations of the string motion are provided to demonstrate the behavior of the model.